Pengaruh Terapi Musik Terhadap Penurunan Nyeri Dismenore Di SMA UII Yogyakarta - Reza Ayu Lestari Lestari; Sri Ratna Ningsih (CV. ITTC INDONESIA, 2025)
Dysmenorrhea has adverse effects, both in the long term and the short term. Music therapy can be an alternative to overcome dysmenorrhea pain. The purpose of this study was to determine the effect of music therapy on reducing dysmenorrhea pain in adolescent girls. The method used is a pre-experiment with a one-group pretest-posttest design approach. The population in this study consisted of 31 female students in grade X, some of whom were then taken as samples using total sampling. The measuring instrument used was the Numeric Rating Scala pain scale, and the statistical test used the Wilcoxon test. The results of the study showed that the pain scale of dysmenorrhea before music therapy was on a moderate pain scale (4-6) for 17 respondents (73%) and a severe pain scale (7-10) for 14 respondents (28%). After the implementation of music therapy, a mild pain scale (1-3) was obtained for 14 respondents (28.5%), moderate pain (4-6) for 16 respondents (72%), and severe pain (7-10) for one respondent (0.5%). The results of the p-value calculation showed a result of 0.000 (<0.05), so Ha was accepted. This study proves the effect of music therapy on reducing pain in dysmenorrhea at SMA UII Yogyakarta